Faktor Yang Memengaruhi Kualitas Audit Internal Dengan Top Management Support Sebagai Variabel Moderasi (Studi Pada Perguruan Tinggi BLU di Indonesia) - Prawira, Yudha; Lismawati, Lismawati; Aisyah, Aisyah (Institut Agama Islam Negeri (IAIN) Curup, 2021)
This study aims to examine the effect of internal auditor competence, internal auditor independence, and internal auditor size on the quality of internal audit auditors of SPI at PTN BLU in Indonesia and to examine whether there is a moderating effect of top management support. The data used in this study are primary data obtained from the results of distributing questionnaires to internal auditors who work in the Internal Control Unit at Higher Education Public Service Bodies in Indonesia. The sampling method used in this study was a census, with 34 respondents. The data analysis method used is moderated regression analysis (MRA). Based on the research results, it is known that: First, the internal auditor's competence has a positive effect on the quality of internal audit. Second, the independence of the internal auditor has a positive effect on the quality of internal audit. Third, internal auditor size has no positive effect on internal audit quality. Fourth, top management support does not moderate the relationship between internal auditor competence, internal auditor independence, and internal auditor size on internal audit quality.